I witness news as it happens citizen journalism and how it is changing the landscape of news reporting - Bana, Rosana A.; Calimquim, Kevin Ian Maniquis; Nano, Lexter Lamsen (2013)
This study is about the effect of citizen journalism on the landscape of news reporting in the Philippines. Specifically, it focuses on two major news networks in the Philippines : GMA and ABS-CBN and how they use different social media and the Internet to gather news from ordinary televiewers who are now called citizen journalists. The research describes the citizen journalism sites of GMA and ABS-CBN (YouScoop and Bayan Mo, Ipatrol Mo: Tayo Na) and analyzes the user generated contents (UGC?s) submitted to both. The bases of analysis are Media Convergence theory by Henry Jenkins and uses and gratification Theory by Elihu Katz and Jay Blumler. The research also includes interviews with media practitioners or both networks as well as the televiewers regarding their perception on city journalism and how it is changing the landscape of new reporting.The results of the study show that citizen journalism is positively influencing and changing the landscape of news reporting in the Philippines. The audience favored the inclusion of citizen journalism in mainstream news reporting because it adds flavor and fresh angles to the news. The audience can also be active participants in the news gathering process. Media practitioners agreed that citizen journalism is helping the media in gathering and disseminating news information through UGC?s submitted by citizen on their online sites and social media pages.
Thesis (Bachelor of Arts in Communication) -- University of the Philippines Baguio, 2013.